Comparative Authority in the Execution of Administrative Court Decisions: Institutional and Compliance Mechanisms in Indonesia and Thailand - Helda Fahira; Ummi Salamah Lubis (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study examines the comparative authority of administrative court decision enforcement in Indonesia and Thailand, focusing on institutional frameworks and compliance mechanisms. Employing a normative juridical method through literature review and statutory analysis, the findings reveal fundamental differences in institutional arrangements. Thailand has established the Legal Execution Department under the Ministry of Justice as a specialized body to enforce court decisions, whereas Indonesia lacks a dedicated execution institution. In terms of compliance, Thailand applies the doctrine of contempt of court, enabling the imposition of criminal sanctions such as imprisonment or administrative fines on non-compliant officials. Indonesia, by contrast, relies primarily on coercive fines (dwangsom), whose effectiveness remains limited. Both countries share the use of dwangsom as a coercive instrument, yet differ in judicial hierarchy: Indonesia operates a three-tier system (First Instance, Appeal, and Cassation), while Thailand maintains a two-tier system (Administrative Court of First Instance and Supreme Administrative Court). This comparative analysis provides recommendations for strengthening Indonesia’s administrative justice system, particularly through the establishment of an execution authority, to ensure effective protection of citizens’ rights.